SOSIAL CONTROL : SIFAT DAN SANKSI SEBAGAI SARANA KONTROL SOSIAL - Sudharma Putra, Ida Bagus (VYAVAHARA DUTA, 2018)
Society in social life always there is a means in the form of control or control to regulate the various behavior or behavior anngota social group, It means that human behavior should be limited by the rules so that humans can know what to do and actions that should not be done. Behavior that is governed means a limit of values ??and norms deviant and antisocial. Con- versely, the behaviors that are ordered mean that they contain values ??and norms that are komformis. Prevention or handling efforts for the community not to violate the rules, then within the community group must have a set of values ??and norms is none other than to prevent or reduce the violation of the rules. This is called the form of social control. When looking at the function of social control that applies to the life of the community, is to develop a fear that someone not to do acts that are not in accordance with the values ??and norms that apply, and provide compensation for people who comply with the values ??and norms -the prevailing norms so as to reinforce a sense of confidence in society that the value is supposed to be adhered to for the life of society towards the better. And able to create a legal system (the rules are formally formulated with the sanctions contained in it). From these limitations, it can be interpreted that social control is a designed or not designed and controlled means and process aimed at engag- ing, educating, and even forcing citizens to comply with prevailing social norms and values.